Student Difficulties in Speaking English Encountered by the Eleventh Grade of Ma Alkhairat Pusat Palu - Widi Alfina; Aminah Suriaman; Zarkiyani Hasyim; Mukrim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The objective of this research is to find out the difficulties in speaking English and the factors that cause the students difficulties in speaking English. This research used a qualitative approach, with findings that were not obtained through statistical procedures or calculations. The type of research design employed was a case study. This research was conducted at Madrasah Aliyah Alkhairat Pusat Palu, Jl. Sis AlJufri, Palu, Central Sulawesi. There are 5 students as participants. The research found that students difficulties in speaking English are influenced by two factors, namely psychological aspects and Speaking Aspects. Psychological aspects consist of fear of mistake, shyness, anxiety and lack of confidence, while language Apects are pronunciation, vocabulary and grammar. The research emphasizes the need to address these issues in the classroom to enhance students’ learning experiences.